SERVICE EXCELLENCE AS THE KEY TO IMPROVING THE COMPETITIVENESS OF CULINARY MSMES IN THE MODERN COMPETITIVE ERA: A QUALITATIVE STUDY IN RT 001 RW 005 KUNINGAN TIMUR, SOUTH JAKARTA - Raden Ai Lutfi Hidayat; Syamsul Anwar; Sulfi Purnamasari (SOSIOEDUKASI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting Indonesia's economic growth, particularly in the culinary sector, which continues to experience rapid competition. In addition to product quality, service quality has become one of the main determinants influencing customer satisfaction and business sustainability. This study aims to analyze the role of service excellence in improving the competitiveness of culinary MSMEs and to identify service improvement solutions through the implementation of service excellence. This research employed a descriptive qualitative approach involving 22 culinary MSME owners located in RT 001 RW 005 Kuningan Timur, Setiabudi District, South Jakarta. Data were collected through observation, in-depth interviews, and documentation, followed by data reduction, data presentation, and conclusion drawing based on the Miles and Huberman interactive analysis model. The findings indicate that service excellence contributes significantly to customer satisfaction, customer loyalty, positive business image, and competitive advantage. The implementation of excellent service through courteous attitudes, prompt responses, professional appearance, responsibility, effective communication, and attention to customer needs encourages repeat purchases and positive word-of-mouth promotion. The study concludes that service excellence should become an integral business strategy for culinary MSMEs to strengthen their competitiveness and business sustainability in the modern business environment.